Upaya Kepala Sekolah Dalam Meningkatkan Kompetensi Profesional Guru PAI di SDN Tambakrejo I Jombang - istighfarin _; Emi Lilawati (Universitas KH. A. Wahab Hasbullah, 2019)
Achieving the objectives of national education will be determined by the skills and proficiency of the teachers in carrying out the learning task. Therefore teachers must have professional competence. But here teachers are competent in their field. So the results of the learning process is already good. This research aims to determine the efforts of the headmaster to improve the professional competency of Islamic education teacher at SDN Tambakrejo I Jombang. The purpose of this research is (1) explaining how the school's efforts to improve the professional competence of PAI teachers at SDN Tambakrejo I Jombang (2) explain how the professional competence of PAI teachers at SDN Tambakrejo I Jombang (3) Explaining the supporting factors and the head of the school's inhibitory factor in enhancing the professional competence of PAI teachers at SDN Tambakrejo I Jombang. The research uses a qualitative and descriptive approach to data collection techniques in the form of observation methods, interview methods, and documentation. While the data analysis technique used by researchers is to use data reduction, data presentation, then the withdrawal of conclusion. From the analysis can be found that the school's efforts to improve the professional competence of PAI teachers at SDN Tambakrejo I Jombang were carried out several things: The principal always provides training or workshops to teachers, head Schools also always give supervision on all teachers, the school principal also provide motivation and appreciation to teachers, personal communication between the school principal and teachers, include training. While the professional competence of PAI teachers at SDN Tambakrejo I Jombang has been quite good. The supporting factor of the school principal in enhancing the professional competence of PAI teachers at SDN Tambakrejo is to foster cooperation between teachers. While the school principal's inhibitory factor in enhancing the professional competence of PAI teachers at SDN Tambakrejo I Jombang is a lack of infrastructure. Keywords : Head of school effort, professional competence of PAI teachers